Intravitreal Bevacizumab for Refractory Pseudophakic Cystoid Macular Edema The Pan-American Collaborative Retina Study Group Results (2009)
Objective: To determine the feasibility, safety, and clinical effect of intravitreal (IVT) bevacizumab (Avastin; Genentech, Inc., San Francisco, CA) in patients with refractory cystoid macular edema (CME) after cataract surgery. Design: Interventional, retrospective, multicenter study.